2015
DOI: 10.1016/j.jtcvs.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in patients undergoing surgery for acute type A aortic dissection

Abstract: There are no differences in early and long-term outcomes between male and female patients undergoing surgery for acute type A aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 36 publications
9
62
3
1
Order By: Relevance
“…Other predictors of long-term mortality may be female sex, and a history of atherosclerosis (28), but these factors did not reach statistical significance in WATAS. Interestingly, WATAS identified a univariate association of male sex with late aortic events, where another study confirmed such univariate association of male sex with late aortic reoperation after AAAD repair (31). Finally, WATAS identified a marginal association of Marfan syndrome with late aortic events, but other studies established Marfan syndrome as an independent predictor of late aortic events (22,32).…”
Section: Other Clinical Predictors Of Late Outcomementioning
confidence: 96%
“…Other predictors of long-term mortality may be female sex, and a history of atherosclerosis (28), but these factors did not reach statistical significance in WATAS. Interestingly, WATAS identified a univariate association of male sex with late aortic events, where another study confirmed such univariate association of male sex with late aortic reoperation after AAAD repair (31). Finally, WATAS identified a marginal association of Marfan syndrome with late aortic events, but other studies established Marfan syndrome as an independent predictor of late aortic events (22,32).…”
Section: Other Clinical Predictors Of Late Outcomementioning
confidence: 96%
“…They found that risk factors for late death were patent distal false lumen, older age, and male sex and risk factors for late aortic events were patent distal false lumen, Marfan syndrome, and distal aorta over 45 mm in diameter. Fukui et al (14) reported a superb early mortality of 5.2% in 504 patients with acute type A dissection over a 7-year period. The TAR was performed in 163 (32.3%) patients.…”
Section: Arch Replacementmentioning
confidence: 99%
“…As in coronary disease, delayed presentation and diagnosis in women due to less typical pain, older age and different comorbidities were described as potential risk factors for a worse outcome in female patients after surgery for AADA [2,5]. In contrast to these findings, female gender was not associated with a worse outcome in recent studies [3,4,12,13]. Several studies on the risk factors for mortality after surgery for AADA included gender as risk factor [4,14], but information about sex-specific risk factors of women and men is rare.…”
Section: Introductionmentioning
confidence: 98%
“…Acute aortic dissection type A (AADA) is one of the major causes of death in cardiovascular disease for women and men [1,2] and requires early surgical treatment to avoid live-threatening complications like aortic rupture, tamponade and malperfusion. Men are affected by AADA about twice as often compared to the incidence in women and present at younger age [2][3][4] and with considerable differences in comorbidities and risk factors [5][6][7]. The impact of gender in cardiovascular surgery has been investigated extensively during the past decades and women were shown to have worse outcomes after coronary bypass surgery [8,9].…”
Section: Introductionmentioning
confidence: 99%